Assessment and Evaluation of IWRM Implementation in Palawan, Philippines - Cacal, Jennifer C.; Taboada, Evelyn B. (Civil Engineering Journal, 2022)
According to the United Nation's Sustainable Development Goal (SDG 6), the world needs to sustainably manage water resources through integrated water resource management (IWRM). The Philippines is committed to this goal by ensuring the implementation of IWRM at all levels. Concurrently, there is growing evidence that there is presently no consolidated data on the status of implementation at the sub-national level. With water shortages on the increase, it's more important than ever to find solutions to settle disputes and trade-offs so that water can be distributed effectively, sustainably, and equally. This paper aims to investigate the degree of implementation of IWRM that presents the actual state of affairs in terms of water management at the sub-national level. This study is focused on Palawan Province, with the following sites: Puerto Princesa City, El Nido, Roxas, and Taytay. A structured survey questionnaire was drawn up in accordance with the existing questionnaire developed for this purpose. The obtained data were computed using the steps developed for calculating the indicators of IWRM implementation degree. Puerto Princesa City, El Nido, Roxas, and Taytay have the following IWRM ratings: 39.93, 32.03, 37.99, and 36.32%, respectively, which means "medium-low" in which the IWRM components have largely been institutionalized, and deployment is well underway. In these regions, a subnational water management scheme exists, but its maximum capacity is mostly unrealized due to numerous constraints. The findings show that the numerous water laws are confusing and that water data for planning purposes is lacking. Even though there are many water agencies, they are not interconnected. This study is useful for successful IWRM implementation, which should encourage sustainable water resource management for environmental sustainability. Integrated methods for water resource management help to organize sustainable growth by assessing how water is handled in agriculture, urban applications, and the surrounding ecosystems.Â Doi: 10.28991/CEJ-2022-08-02-08 Full Text: PDF